Tutoring rówieśniczy w pracy z grupą uczniów o zróżnicowanych potrzebach edukacyjnych - Parys, Katarzyna; Olszewski, Sławomir (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Peer tutoring is one of the solutions that should be taken into account when working with a group of students with diverse educational needs. This study attempts to organize information about peer tutoring and describe its selected implementation variants, taking into account the necessary educational recommendations. The validity and possibilities of using modifications in tutoring activities allowing for the development of solutions that will meet the needs and capabilities of each student in a diverse group were also indicated.
Keywords: zróżnicowane potrzeby edukacyjne; wzajemny tutoring rówieśniczy; tutoring rówieśniczy w całej klasie; strategie uczenia się wspomaganego przez rówieśników; tutoring rówieśniczy bez wymiany ról; tutoring rówieśniczy osób w różnym wieku; tutoring z odwróconymi rolami; tutoring rówieśniczy dla osób w tym samym wieku; diverse educational needs; Reciprocal Peer Tutoring (RPT); Classwide Peer Tutoring (CWPT); Peer Assisted Learning Strategies (PALS); peer tutoring without role exchange; Cross-Age Peer Tutoring; Reverse-role tutoring; Same-Age Peer Tutoring